A full-solid-waste-based pre-mixed fluid mud solidifying agent and a preparation method thereof
Patent Information
- Application Number
- CN202310771948.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-28
AI Technical Summary
[0047](1)本发明所述的全固废基的预拌流态泥浆固化剂通过工业固废复合激发剂制备得到,使用时在不同龄期均具有一定的力学强度,满足使用要求;与水泥作为固化胶凝材料相比,成本更加低廉,大幅度的减少了碳排放,实现了工业固废的资源化利用,产生良好的社会效益与经济效益;
Smart Images

Figure CN116803946B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, and in particular relates to a premixed fluidized mud solidifier based on all-solid waste and its preparation method. Background Technology
[0002] Premixed fluidized mud slurry for soil stabilization offers advantages such as adjustability and controllability, good stability, convenient construction, and low carbon footprint. Therefore, it has been widely used in infrastructure backfilling projects, such as highway subgrades, pipe gallery trenches, and foundation pits. The use of premixed fluidized mud slurry effectively solves problems that may arise in traditional backfilling projects, such as dust generation, construction inconvenience, and poor compaction.
[0003] Early premixed fluid slurry curing agents typically used pure composite cement and ordinary Portland cement. With the emergence of various mineral admixtures, mineral-based curing agents for composite Portland cements made from fly ash, mineral powder, and coal gangue have been widely used.
[0004] In order to dispose of solid waste and achieve green and sustainable development, if low-carbon cementitious materials can be prepared from solid waste as solidifying agents for premixed fluid slurry, it will help reduce carbon emissions, achieve the goal of green, circular and sustainable development in the building materials industry, reduce costs, and generate good social and economic benefits. Summary of the Invention
[0005] In view of this, to solve the above problems, this invention proposes a premixed fluidized mud solidifier based on all solid waste and its preparation method, realizing the resource utilization of industrial solid waste. Compared with cement as a solidifying cementitious material, it has a lower cost, significantly reduces carbon emissions, and generates good social and economic benefits. The premixed fluidized mud solidifier based on all solid waste, prepared by using industrial solid waste composite activator, can solidify premixed fluidized mud to form pumpable premixed fluidized solidified soil, simplifying the construction process in backfilling projects, improving construction efficiency, and reducing backfilling costs.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0007] The present invention provides a premixed fluidized mud solidifier based on solid waste, comprising the following raw material components by weight: 30-35 parts of granulated blast furnace slag powder; 15-20 parts of calcium carbide slag powder; 13-18 parts of ultrafine steel slag powder; 15-19 parts of lightly calcined desulfurized gypsum; 5-15 parts of harmless aluminum ash; and 1-5 parts of activator.
[0008] In some preferred embodiments of the premixed fluidized mud solidifier based on all-solid waste of the present invention, the granulated blast furnace slag powder is of grade S95.
[0009] In some preferred embodiments of the premixed fluidized mud solidifier based on all solid waste of the present invention, the calcium carbide slag powder has a particle size of less than 0.075 mm.
[0010] In some preferred embodiments of the premixed fluidized mud solidifier based on all-solid waste of the present invention, the specific surface area of the steel slag ultrafine powder is 700 m². 2 With a content of over / Kg, it serves as an auxiliary gelling material and exhibits high activity. Compared to ordinary steel slag powder, its 28-day activity index can reach 100%.
[0011] In some preferred embodiments of the premixed fluidized mud solidifier based on solid waste of the present invention, the lightly calcined desulfurized gypsum is anhydrous gypsum (CaSO4) or hemihydrate gypsum (CaSO4·1 / 2H2O) that has been lightly calcined at 300-350°C. Such gypsum after light calcination has a good coagulation effect.
[0012] In some preferred embodiments of the premixed fluidized mud solidifier based on solid waste of the present invention, the harmless aluminum ash is obtained by wet treatment of secondary aluminum ash, which is harmless and pollution-free to the environment and does not belong to the category of hazardous waste.
[0013] In some preferred embodiments of the premixed fluidized mud solidifier based on all-solid waste of the present invention, the granulated blast furnace slag powder is obtained by the following method: during pig iron smelting, at a temperature of 1400-1600°C, a fusible mixture formed by the reaction of gangue, ash, flux, and other impurities is obtained, followed by water quenching to obtain active granulated blast furnace slag, which is then ground and screened to obtain a specific surface area of 400-450 m². 2 / kg of S95 grade granulated blast furnace slag powder was used as a silica-alumina raw material.
[0014] In some preferred embodiments of the premixed fluidized mud solidifier based on solid waste of the present invention, the calcium carbide slag powder is obtained by drying the water-containing waste residue generated during the production of acetylene chemical raw materials from calcium carbide, and then crushing, grinding and sieving to obtain calcium carbide slag powder with a particle size of less than 0.075 mm as a calcium-based raw material.
[0015] In some preferred embodiments of the premixed fluidized mud solidifier based on all-solid waste of the present invention, the ultrafine steel slag powder is obtained as follows: During the steelmaking process, industrial waste generated at 1500–1700°C and after quenching is taken, crushed, screened, impact-milled, graded, and magnetically separated to obtain steel slag powder with a particle size less than 0.075 mm. This steel slag powder is then ground using an ultrafine ball mill system until its specific surface area is 700 m². 2 / Kg or more, to obtain highly active steel slag ultrafine powder as an auxiliary gelling material, the steel slag ultrafine powder has a 28-day activity index of up to 100% compared with ordinary steel slag powder.
[0016] In some preferred embodiments of the premixed fluidized mud solidifier based on solid waste of the present invention, the lightly calcined desulfurized gypsum is obtained by grinding flue gas desulfurized gypsum (CaSO4·2H2O), sieving it after milling, and then lightly calcining it at 300-350°C to make it hemihydrate gypsum (CaSO4·1 / 2H2O) or anhydrous gypsum (CaSO4). The lightly calcined desulfurized gypsum obtained by light calcination has a good coagulation effect.
[0017] In some preferred embodiments of the premixed fluidized mud solidifying agent based on solid waste of the present invention, the harmless aluminum ash is obtained by the following method: firstly, nitrogen is removed from the aluminum ash to obtain secondary aluminum ash, and then fluorine is removed from the secondary aluminum ash by alkaline leaching to obtain harmless aluminum ash. The aluminum ash that has been harmlessly treated is no longer classified as hazardous waste and can be used as an aluminum raw material.
[0018] In some preferred embodiments of the premixed fluidized mud solidifying agent based on solid waste of the present invention, the activator is powdered sodium silicate (Na2O(SiO2)x·yH2O, Na2O≥18%, SiO2≥60%) or adipic acid, which has good activation effect and does not cause alkali return.
[0019] In some preferred embodiments of the premixed fluidized mud solidifier based on all-solid waste of the present invention, by mass percentage:
[0020] The main chemical composition of the granulated blast furnace slag powder is as follows: CaO 41.34%, SiO2 33.67%, Al2O3 14.52%, Fe2O3 0.33%, MgO 6.18%, Na2O 0.42%, K2O 0.38%, f-CaO 0.54%, LOI 0.77%;
[0021] The main chemical composition of the calcium carbide slag powder is as follows: CaO 75.89%, SiO2 3.14%, Al2O3 1.56%, Fe2O3 0.21%, MgO 0.18%, Na2O 1.22%, K2O 0.53%, SO3 0.61%, f-CaO 0.50%, LOI 16.16%;
[0022] The main chemical composition of the ultrafine steel slag powder is as follows: CaO 46.12%, SiO2 13.64%, Al2O3 4.21%, Fe2O3 8.68%, MgO 10.84%, Na2O 0.32%, K2O 0.12%, P2O5 2.75%, f-CaO 11.44%, LOI 1.79%;
[0023] The main chemical composition of the light-calcined desulfurized gypsum is as follows: CaO 42.18%, SiO2 2.74%, Al2O3 2.06%, Fe2O3 0.34%, MgO 1.47%, Na2O 0.13%, K2O 0.16%, SO3 49.83%, TiO2 0.13%, P2O5 0.04%, f-CaO 0.38%, LOI 0.54%;
[0024] The main chemical composition of the harmless aluminum ash is as follows: CaO 1.73%, SiO2 1.28%, Al2O3 1.23%, Fe2O3 1.46%, MgO 7.49%, Na2O 0.32%, K2O 0.44%, TiO2 1.35%, f-CaO 1.82%, and LOI 2.88%.
[0025] A second aspect of this invention provides a method for preparing a premixed fluidized mud solidifier based entirely on solid waste, comprising the following steps:
[0026] S1. Pre-treat industrial solid waste raw materials to obtain granulated blast furnace slag powder, calcium carbide slag powder, steel slag ultrafine powder, light-burned desulfurized gypsum, and harmless aluminum ash;
[0027] S2. Weigh the following raw material components by weight: 30-35 parts granulated blast furnace slag powder; 15-20 parts calcium carbide slag powder; 13-18 parts ultrafine steel slag powder; 15-19 parts light-burned desulfurized gypsum; 5-15 parts harmless aluminum ash; 1-5 parts activator.
[0028] S3. Mix the weighed raw material components evenly and ball mill at 250-300 rpm to make the activator evenly adhere to the surface of the other raw material components, thereby improving the hydration activity and obtaining the curing agent.
[0029] In some preferred embodiments of the preparation method of the premixed fluidized mud solidifier based on all-solid waste of the present invention, the pretreatment method in S1 is as follows:
[0030] Granulated blast furnace slag powder: During pig iron smelting, at a temperature of 1400–1600℃, a fusible mixture formed by the reaction of gangue, ash, flux, and other impurities is taken. This fusible mixture is then subjected to water quenching and extreme cooling to obtain active granulated blast furnace slag. After grinding, the slag is screened to have a specific surface area of 400–450 m². 2 / Kg of S95 grade granulated blast furnace slag powder was used as a silica-alumina raw material.
[0031] Calcium carbide slag powder: The waste residue containing moisture produced during the production of acetylene chemical raw materials from calcium carbide is dried, then crushed, ground, and sieved to obtain calcium carbide slag powder with a particle size of less than 0.075mm, which is used as a calcium-based raw material.
[0032] Steel slag ultrafine powder: During the steelmaking process, industrial waste generated at 1500–1700℃ and after quenching is collected. After crushing, screening, impact grinding, grading, and magnetic separation, steel slag powder with a particle size less than 0.075mm is obtained. This powder is then further ground using an ultrafine ball mill system to a specific surface area of 700m². 2 / kg or more, to obtain highly active steel slag ultrafine powder as an auxiliary cementing material;
[0033] Lightly calcined desulfurization gypsum: The flue gas desulfurization gypsum (CaSO4·2H2O) is ground, sieved after milling, and then lightly calcined at 300-350℃ to become hemihydrate gypsum (CaSO4·1 / 2H2O) or anhydrous gypsum (CaSO4). The lightly calcined desulfurization gypsum obtained through light calcination has a good coagulation effect.
[0034] Harmless aluminum ash: First, nitrogen is removed from the aluminum ash to obtain secondary aluminum ash. Then, fluorine is removed from the secondary aluminum ash by alkaline leaching to obtain harmless aluminum ash. Aluminum ash that has undergone harmless treatment is no longer classified as hazardous waste and can be used as an aluminum raw material.
[0035] In some preferred embodiments of the preparation method of the premixed fluidized mud solidifying agent based on solid waste of the present invention, the activator is powdered sodium silicate (Na2O(SiO2)x·yH2O, Na2O≥18%, SiO2≥60%) or adipic acid; powdered sodium silicate is alkaline and adipic acid is acidic, both have good activation effect and neither will cause alkali return.
[0036] The third aspect of the present invention provides a premixed fluidized mud solidified soil, which is a pumpable premixed fluidized mud solidified soil formed by mixing slag soil with a moisture content of 35-40% and adding the premixed fluidized mud solidified agent based on all solid waste. The amount of the premixed fluidized mud solidified agent based on all solid waste added is 20%-30% of the weight of the slag soil.
[0037] The fourth aspect of this invention provides a method for preparing premixed fluidized mud slurry solidified soil, wherein slag soil with a moisture content of 35-40% is slurried; and then the premixed fluidized mud slurry solidifying agent based on all solid waste is added to form pumpable premixed fluidized mud slurry solidified soil; wherein the amount of the premixed fluidized mud slurry solidifying agent based on all solid waste is 20%-30% of the weight of the slag soil.
[0038] The mechanism of action of the premixed fluidized mud solidifier described in this invention is as follows:
[0039] The harmless aluminum ash, granulated blast furnace slag powder, and calcium carbide slag powder contained in the raw materials of the premixed fluidized mud solidifier provide the aluminum source, silicon source, and calcium hydroxide required for the 'volcanic ash' effect, respectively. The specific chemical reaction in the presence of the activator is as follows:
[0040] Potential reaction between aluminum ash and calcium carbide slag powder: Ca(OH)2 + Al2O3 + H2O → CAH
[0041] Potential reaction between granulated blast furnace slag powder and calcium carbide slag powder: Ca(OH)2 + SiO2 + H2O → CSH
[0042] The reaction of calcium carbide slag powder, harmless aluminum ash and lightly calcined desulfurized gypsum:
[0043]
[0044] Potential reaction for gel formation during hydration of ultrafine steel slag powder: C3S(C2S) + H2O → CS-H + CH
[0045] The various hydration gels produced by the above reactions enable the premixed fluidized mud curing agent to have certain mechanical strength at different ages.
[0046] Compared with existing technologies, the premixed fluidized mud solidifier based on all-solid waste and its preparation method described in this invention have the following advantages:
[0047] (1) The premixed fluid slurry solidifying agent based on solid waste described in this invention is prepared by industrial solid waste composite activator. It has certain mechanical strength at different ages when used, which meets the requirements for use. Compared with cement as a solidifying cementitious material, it is cheaper, significantly reduces carbon emissions, realizes the resource utilization of industrial solid waste, and generates good social and economic benefits.
[0048] (2) The premixed fluid slurry solidifying agent based on solid waste described in this invention can solidify the premixed fluid slurry to form a pumpable premixed fluid solidified soil, which can simplify the construction process in backfilling projects, improve construction efficiency, and reduce backfilling costs.
[0049] (3) The premixed fluidized mud solidifying agent based on all solid waste described in this invention uses a specific surface area of 400-450 m². 2 / kg of S95 grade granulated blast furnace slag powder was used as the siliceous-aluminous raw material; ultrafine steel slag powder with a particle size of less than 0.075mm was used as the calcareous raw material; and a specific surface area of 700m² was used. 2 Highly active ultrafine steel slag powder with an activity level of over / Kg is used as an auxiliary gelling material. Compared with ordinary steel slag powder, the activity index of ultrafine steel slag powder can reach 100% after 28 days. Lightly calcined desulfurized gypsum is used to provide good coagulation effect. Harmless aluminum ash after harmless treatment is used as aluminum raw material. Powdered sodium silicate or adipic acid, which does not cause alkali return and has good activation effect, is used as activator. The resulting premixed fluidized mud solidifier has good mud solidification performance and meets mechanical strength requirements. Attached Figure Description
[0050] Figure 1 This is a schematic diagram illustrating the mechanism of action of the premixed fluidized mud solidifier described in this invention;
[0051] Figure 2 This refers to the solidification process of the premixed fluid slurry described in this invention. Detailed Implementation
[0052] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0053] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.
[0054] Examples 1-3
[0055] In Examples 1-3, unless otherwise specified, the all-solid waste-based premixed fluidized mud solidifiers were prepared in the following manner:
[0056] Step 1: Pre-treatment of industrial solid waste raw materials:
[0057] Granulated blast furnace slag powder: During pig iron smelting, at a temperature of 1400–1600℃, a fusible mixture formed by the reaction of gangue, ash, flux, and other impurities is taken. This fusible mixture is then subjected to water quenching and extreme cooling to obtain active granulated blast furnace slag. After grinding, the slag is screened to have a specific surface area of 400–450 m². 2 / kg of S95 grade granulated blast furnace slag powder;
[0058] Calcium carbide slag powder: The waste residue containing moisture generated during the production of chemical raw materials such as acetylene from calcium carbide is dried in a drying oven at 105℃ for 2.0h, and then mechanically crushed and ground and passed through a 200-mesh sieve to obtain calcium carbide slag powder with a particle size of less than 0.075mm.
[0059] Steel slag ultrafine powder: During the steelmaking process, industrial waste generated at 1500–1700℃ and after quenching is collected. After crushing, screening, impact grinding, grading, and magnetic separation, steel slag powder with a particle size less than 0.075mm is obtained. This powder is then further ground using an ultrafine ball mill system to a specific surface area of 700m². 2 / kg or more, to obtain highly active steel slag ultrafine powder;
[0060] Lightly calcined desulfurized gypsum: The flue gas desulfurized gypsum is fed into a Fahrenheit mill for grinding. After being screened after milling, it is lightly calcined in a muffle furnace at 300-350℃ to make it into hemihydrate gypsum or anhydrous gypsum, thus obtaining lightly calcined desulfurized gypsum.
[0061] Harmless aluminum ash: Aluminum ash is calcined at 800℃ for about 60 minutes to remove AlN, yielding secondary aluminum ash. This secondary aluminum ash is then defluorinated using an alkaline leaching method, first soaked in 10% NaOH for 24 hours, followed by the addition of a small amount of CaO for fluorination. - Ion precipitation yields harmless aluminum ash;
[0062] The main chemical compositions of the obtained granulated blast furnace slag powder, calcium carbide slag powder, steel slag ultrafine powder, lightly calcined desulfurized gypsum, and harmless aluminum ash are shown in Table 1.
[0063] Table 1 Chemical composition of industrial solid waste
[0064]
[0065]
[0066] Step 2: Weigh the raw material components according to the weight proportions shown in Table 2;
[0067] Table 2. Ingredient list of premixed fluidized mud solidifying agent based on all solid waste as described in Examples 1-3.
[0068]
[0069] S3. The weighed raw material components are mixed evenly by a mixer and then ball-milled for 15 minutes at 250-300 rpm by a planetary ball mill to ensure that the activator is evenly attached to the surface of the other raw material components, thereby obtaining the premixed fluidized mud solidifying agent based on solid waste.
[0070] Comparative Example 1
[0071] A company's commercially available mineral-based mud curing material.
[0072] Performance Test Experiment 1
[0073] The mechanical property test specimens were prepared using the following method:
[0074] 1) After the slag soil with a moisture content of 35% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 1 is added, and the amount added is 30% of the weight of the slag soil, to obtain the premixed fluid slurry hardening specimen 1.
[0075] 2) After the slag with a moisture content of 35% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 2 is added, and the amount added is 30% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 2.
[0076] 3) After the slag with a moisture content of 35% is slurryed, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 3 is added, and the amount added is 30% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 3.
[0077] 4) After the slag with a moisture content of 35% is slurryed, a commercially available mineral-based mud solidification material from a certain company is added to Comparative Example 1 at a rate of 30% of the weight of the slag, thus obtaining Commercial Comparative Example 1.
[0078] Mechanical properties were tested on premixed fluidized mud hardening specimens 1-3 and commercially available control specimen 1. The test results are shown in Table 3.
[0079] Table 3 Mechanical properties of hardened specimens (1)
[0080]
[0081] Performance Test Experiment 2
[0082] The mechanical property test specimens were prepared using the following method:
[0083] 1) After the slag with a moisture content of 40% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 1 is added, and the amount added is 20% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 4.
[0084] 2) After the slag with a moisture content of 40% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 2 is added. The amount added is 20% of the weight of the slag, and the premixed fluid slurry hardening specimen 5 is obtained.
[0085] 3) After the slag with a moisture content of 40% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 3 is added, and the amount added is 20% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 6.
[0086] 4) After the slag with a moisture content of 40% is slurried, a commercially available mineral-based mud solidification material from a certain company is added to the slag, with the addition amount being 20% of the weight of the slag, to obtain the commercially available comparative sample 2.
[0087] Mechanical properties were tested on premixed fluidized mud hardening specimens 4-6 and commercially available control specimen 2. The test results are shown in Table 4.
[0088] Table 4 Mechanical properties of hardened specimens (2)
[0089]
[0090] Performance Test Experiment 3
[0091] The mechanical property test specimens were prepared using the following method:
[0092] 1) After the slag soil with a moisture content of 35% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 1 is added, and the amount added is 30% of the weight of the slag soil, to obtain the premixed fluid slurry hardening specimen 7.
[0093] 2) After the slag with a moisture content of 35% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 2 is added, and the amount added is 30% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 8.
[0094] 3) After the slag with a moisture content of 35% is slurried, the premixed fluid slurry solidifying agent with all solid waste base prepared in Example 3 is added, and the amount added is 30% of the weight of the slag, to obtain the premixed fluid slurry hardening specimen 9.
[0095] 4) After the slag with a moisture content of 35% is slurryed, a commercially available mineral-based mud solidification material from a certain company is added to the slag, with the addition amount being 30% of the weight of the slag, to obtain the commercially available comparative sample 3.
[0096] Mechanical properties were tested on premixed fluidized mud hardening specimens 7-9 and commercially available control specimen 3. The test results are shown in Table 5.
[0097] Table 5 Mechanical properties of hardened specimens (3)
[0098]
[0099]
[0100] The data above show that the all-solid waste-based premixed fluidized mud solidifiers prepared in Examples 1-3 all exhibit good mud solidification performance and meet the mechanical strength requirements. In particular, the all-solid waste-based premixed fluidized mud solidifier prepared in Example 3 shows the best effect. Its mechanism of action is as follows: Figure 1 As shown ( Figure 1 The diagram also illustrates the case where the activator is anhydrous sodium silicate.
[0101] Example 4
[0102] Preparation process of pumpable premixed fluidized mud solidified soil:
[0103] like Figure 2 As shown, the slag soil with a moisture content of 35-40% is first slurryed; then the premixed fluid slurry solidifying agent based on solid waste is added (the amount added is 20%-30% of the weight of the slag soil) to form a pumpable premixed fluid slurry solidified soil.
[0104] Premixed fluid slurry solidified soil is backfilled into highway subgrade, pipe gallery trench and foundation pit by pumping.
[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A premixed fluidized mud solidifier based entirely on solid waste, characterized in that, The raw material components include the following by weight: 30-35 parts granulated blast furnace slag powder; 15-20 parts calcium carbide slag powder; 13-18 parts ultrafine steel slag powder; 15-19 parts light-burned desulfurized gypsum; 5-15 parts harmless aluminum ash; and 1-5 parts activator. The granulated blast furnace slag powder is grade S95; the calcium carbide slag powder has a particle size of less than 0.075 mm; and the steel slag ultrafine powder has a specific surface area of 700 m². 2 / Kg or more; the lightly calcined desulfurized gypsum is anhydrous or hemihydrate gypsum that has been lightly calcined at 300-350℃; the harmless aluminum ash is obtained by wet treatment of secondary aluminum ash. The harmless aluminum ash is obtained by the following method: first, nitrogen is removed from the aluminum ash to obtain secondary aluminum ash, and then fluorine is removed from the secondary aluminum ash by alkaline leaching to obtain harmless aluminum ash. The activator is powdered sodium silicate or adipic acid.
2. The premixed fluidized mud solidifier based on all solid waste according to claim 1, characterized in that: The granulated blast furnace slag powder is obtained as follows: during pig iron smelting, at a temperature of 1400–1600℃, a fusible mixture formed by the reaction of gangue, ash, flux, and other impurities is obtained. This mixture is then subjected to water quenching to achieve high reactivity, resulting in granulated blast furnace slag. After grinding and screening, a specific surface area of 400–450 m² is obtained. 2 / kg of S95 grade granulated blast furnace slag powder; The calcium carbide slag powder is obtained by drying the moisture-containing waste residue generated during the production of acetylene chemical raw materials from calcium carbide, and then crushing, grinding and sieving to obtain calcium carbide slag powder with a particle size of less than 0.075 mm.
3. The premixed fluidized mud solidifier based on all solid waste according to claim 1, characterized in that: The ultrafine steel slag powder is obtained as follows: During the steelmaking process, industrial waste generated at 1500-1700℃ and after quenching is taken, crushed, screened, impact-milled, classified, and magnetically separated to obtain steel slag powder with a particle size of less than 0.075mm. The steel slag powder is then ground into a finer powder using an ultrafine ball milling system until its specific surface area is 700m². 2 / kg or more, to obtain highly active steel slag ultrafine powder; The lightly calcined desulfurized gypsum is obtained by grinding flue gas desulfurized gypsum, screening it after milling, and then lightly calcining it at 300-350℃ to make it into hemihydrate gypsum or anhydrous gypsum, thus obtaining lightly calcined desulfurized gypsum.
4. The premixed fluidized mud solidifier based on all solid waste according to claim 1, characterized in that, By weight percentage: The main chemical composition of the granulated blast furnace slag powder is as follows: CaO 41.34%, SiO2 33.67%, Al2O3 14.52%, Fe2O3 0.33%, MgO 6.18%, Na2O 0.42%, K2O 0.38%, f-CaO 0.54%, LOI 0.77%; The chemical composition of the calcium carbide slag powder is as follows: CaO 75.89%, SiO2 3.14%, Al2O3 1.56%, Fe2O3 0.21%, MgO 0.18%, Na2O 1.22%, K2O 0.53%, SO3 0.61%, f-CaO 0.50%, LOI 16.16%; The main chemical composition of the ultrafine steel slag powder is as follows: CaO 46.12%, SiO2 13.64%, Al2O3 4.21%, Fe2O3 8.68%, MgO 10.84%, Na2O 0.32%, K2O 0.12%, P2O5 2.75%, f-CaO 11.44%, LOI 1.79%; The chemical composition of the lightly calcined desulfurized gypsum is as follows: CaO 42.18%, SiO2 2.74%, Al2O3 2.06%, Fe2O3 0.34%, MgO 1.47%, Na2O 0.13%, K2O 0.16%, SO3 49.83%, TiO2 0.13%, P2O5 0.04%, f-CaO 0.38%, LOI 0.54%; The chemical composition of the harmless aluminum ash is as follows: CaO 1.73%, SiO2 1.28%, Al2O3 1.23%, Fe2O3 1.46%, MgO 7.49%, Na2O 0.32%, K2O 0.44%, TiO2 1.35%, f-CaO 1.82%, LOI 2.88%.
5. The preparation method of the premixed fluidized mud solidifier based on all solid waste as described in claim 1, characterized in that, Includes the following steps: S1. Pre-treat industrial solid waste raw materials to obtain granulated blast furnace slag powder, calcium carbide slag powder, steel slag ultrafine powder, light-burned desulfurized gypsum, and harmless aluminum ash; S2. Weigh the following raw material components by weight: 30-35 parts granulated blast furnace slag powder; 15-20 parts calcium carbide slag powder; 13-18 parts ultrafine steel slag powder; 15-19 parts light-burned desulfurized gypsum; 5-15 parts harmless aluminum ash; 1-5 parts activator. S3. Mix the weighed raw material components evenly, and ball mill at 250-300 rpm to make the activator evenly adhere to the surface of the other raw material components, thereby obtaining the curing agent.
6. The method for preparing the all-solid waste-based premixed fluidized mud solidifier according to claim 5, characterized in that: The preprocessing method in S1 is as follows: Granulated blast furnace slag powder: During pig iron smelting, at a temperature of 1400–1600℃, a fusible mixture formed by the reaction of gangue, ash, flux, and other impurities is taken. This fusible mixture is then subjected to water quenching and extreme cooling to obtain active granulated blast furnace slag. After grinding, the slag is screened to have a specific surface area of 400–450 m². 2 / kg of S95 grade granulated blast furnace slag powder; Calcium carbide slag powder: The waste residue containing moisture produced during the production of acetylene chemical raw materials from calcium carbide is dried, then crushed, ground, and sieved to obtain calcium carbide slag powder with a particle size of less than 0.075 mm. Ultrafine steel slag powder: This is produced during the steelmaking process, using industrial waste generated at 1500–1700℃ and after quenching. After crushing, screening, impact grinding, grading, and magnetic separation, steel slag powder with a particle size less than 0.075mm is obtained. This powder is then further ground using an ultrafine ball mill system to achieve a specific surface area of 700 m². 2 / kg or more, to obtain highly active steel slag ultrafine powder; Lightly calcined desulfurized gypsum: The flue gas desulfurization gypsum is ground, sieved after milling, and then lightly calcined at 300-350℃ to make it into hemihydrate gypsum or anhydrous gypsum, thus obtaining lightly calcined desulfurized gypsum. Harmless aluminum ash: First, nitrogen is removed from the aluminum ash to obtain secondary aluminum ash. Then, fluorine is removed from the secondary aluminum ash by alkaline leaching to obtain harmless aluminum ash.
7. The method for preparing the premixed fluidized mud solidifier based on all solid waste according to claim 5, characterized in that: The activator is powdered sodium silicate or adipic acid.
8. A premixed fluidized mud-stabilized soil, characterized in that: It is a pumpable premixed fluid slurry solidified soil made by mixing slag soil with a moisture content of 35-40% and adding the premixed fluid slurry solidifying agent of all solid waste as described in any one of claims 1 to 4; the amount of the premixed fluid slurry solidifying agent of all solid waste as added is 20%-30% of the weight of the slag soil.
9. A method for preparing premixed fluidized mud-stabilized soil, characterized in that: The slag soil with a moisture content of 35-40% is slurried; then the premixed fluid slurry solidifying agent based on any one of claims 1 to 4 is added to form a pumpable premixed fluid slurry solidified soil; the amount of the premixed fluid slurry solidifying agent based on the all-solid waste is 20%-30% of the weight of the slag soil.
Citation Information
Patent Citations
Solid waste cementing material, all-solid-waste concrete and preparation method thereof
CN112250329A
Method for synergistically preparing foundation pit backfill material by utilizing multi-element solid waste
CN115259817A
All-solid-waste-based low-carbon green ecological cementing material and manufacturing method thereof
CN115321848A